2021
DOI: 10.1098/rsos.201627
|View full text |Cite
|
Sign up to set email alerts
|

Goats show higher behavioural flexibility than sheep in a spatial detour task

Abstract: The ability to adapt to changing environments is crucial for survival and has evolved based on socio-ecological factors. Goats and sheep are closely related, with similar social structures, body sizes and domestication levels, but different feeding ecologies, i.e. goats are browsers and sheep are grazers. We investigated whether goats' reliance on more patchily distributed food sources predicted an increased behavioural flexibility compared to sheep. We tested 21 goats and 28 sheep in a spatial A-not-B detour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Further, it is noticeable that the fixed effect of slope on goats is lower than sheep, which means that sheep husbandry might be more sensitive to geomorphic change. It could be supported by recent animal science literature that compared to sheep, goat is more adaptive in mountainous and hilly regions (Raoult, et al, 2021).…”
Section: Importance Of Geomorphic and Social-economic Factors In Sheep And Goat Distributionsmentioning
confidence: 86%
“…Further, it is noticeable that the fixed effect of slope on goats is lower than sheep, which means that sheep husbandry might be more sensitive to geomorphic change. It could be supported by recent animal science literature that compared to sheep, goat is more adaptive in mountainous and hilly regions (Raoult, et al, 2021).…”
Section: Importance Of Geomorphic and Social-economic Factors In Sheep And Goat Distributionsmentioning
confidence: 86%
“…Studies on drugs abuse in laboratory rodents (mice and rats) have suggested that generally males have more difficulties in inhibiting prepotent responses compared to females (reviewed in Weafer & deWit, 2014). In the A-not-B task, in which subjects had to deal with a stimulus that changed position across different trials, goats did not show sex differences (Raoult et al, 2021). Last, studies on dogs' inhibitory control reported quite consistently a similar performance in males and females with various tasks: cylinder task and A-not-B task (Faganani et al, 2016); a task requiring to ignore a preferred, but unobtainable, food reward (Bray et al, 2014); a battery of three inhibitory tasks (Brucks et al, 2017).…”
Section: Cognitive Flexibility and Inhibitory Control In Mammalsmentioning
confidence: 88%
“…Meyer et al 2012, Nawroth et al 2014). However, behavioural flexibility is more commonly inferred from how well animals can inhibit or control a behaviour of interest or through their performance in reversal learning tasks (Nawroth et al 2016a, Raoult et al 2021, both of which have been explored in a variety of contexts in goats.…”
Section: Behavioural Flexibilitymentioning
confidence: 99%
“…However, despite the wide use of this task, given performance can vary according to an individual animal's experience with or understanding of artificial, transparent barriers, its ecological validity is questionable (van Horik et al 2018). In an arguably more ecologically valid task, goats (but not all sheep) were shown to immediately detour around a physical barrier to retrieve food, despite momentarily increasing the distance between itself and the reward (Raoult et al 2021, Nawroth et al 2016a).…”
Section: Behavioural Flexibilitymentioning
confidence: 99%